Peer-to-Peer Networks: A Language Theoretic Approach - Lázár, Katalin; Varjú, Erzsébet Csuhaj; Lörincz, András (Computing and Informatics, 2012)
In this article a modification of a grammar systems theoretic construction, the so-called network of parallel language processors, is proposed to describe the behaviour of peer-to-peer (P2P) systems. In our model, the language processors form teams, send and receive information through collective and individual filters. The paper deals with the dynamics of string collections. The connection between the growth function of a developmental system and the growth function of networks of parallel multiset string processors with teams of collective and individual filtering is also established.